HAK PENDERITA HIV DALAM PERSPEKTIF HAM - Ari Rahmat Elsad; Gunawan Widjaja (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to describe the protection of human rights and the prohibition of discrimination as well as efforts to implement the prohibition of discrimination against people living with HIV. The research method used is a normative research method using literature study through the use of secondary data. The results obtained show that people living with HIV do not receive legal justice for their survival so that regulations are needed to protect them. The conclusion of the study shows that although there are regulations that protect people living with HIV, in practice, this protection of human rights is often contradicted and interpreted to protect the interests of the human rights of an individual without paying attention to the rights of others. Therefore, the provision of directed and integrated communication, information and education about HIV to the wider community is also needed as a companion in upholding human rights protection for people living with HIV.